Pengembangan materi ajar Balaghah berbasis pendekatan kontrastif - Nurbayan, Yayan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
Difficulties in understanding Arabic Balaghah is common among Indonesian students learning Arabic. One of the factors attributable to the difficulties is the different characteristics of Arabic and Indonesia. This contrastive research aimed at developing more understandable materials for the study of Balaghah. The research used a quasi-experimental method. Based on the questionnaires distributed, the respondents considered that lectures using contrastive materials for the study of Balaghah were easier and more understandable.